Model and online calculator for prediction of fistula maturation based on vein dilation and age: A retrospective cohort study in a single-center - Jing Sun; Pu-ping Hu; Shen Zhan; Rui Cui; Fang Hou; Yu-zhu Wang (Asian Journal of Surgery, 2023)
Objective: A model that considers the characteristics of dialysis patients may help predict successful fistula maturation. We evaluated factors associated with radiocephalic arteriovenous fistula (RCAVF) maturation at 3 months in dialysis patients with end-stage renal disease (ESRD). Methods: A total of 184 patients who received an initial RCAVF at Beijing Haidian Hospital (Haidian Section of Peking University Third Hospital) were recruited. Fistula maturation was assessed within 3 months. Patient characteristics and preoperative vascular assessment indices were examined. Factors associated with fistula maturation were analyzed using logistic regression and least absolute shrinkage and selection operator (LASSO) binary logistic regression. Boostrapping was used for internal validation. Results: The development data consisted of 184 ESRD patients receiving an initial RCAVF, 140 (76%) of whom achieved fistula maturation. The main predictors of RCAVF maturation in the final model were sex, age-adjusted vein dilation (eVD), radial artery volume (Vartery), and diastolic blood pressure. The difference of vein diameter with and without a tourniquet was significantly larger in the mature RCAVF group (3.0 ± 0.5 vs. 2.2 ± 0.5 mm). The area under receiver operating characteristic (AUROC) curve for prediction of fistula maturation was 0.77, and the Hosmer-Lemeshow statistic indicated agreement between observed and predicted values (P = 0.792). Analysis of internal validation using bootstrapping indicated the C-index was 0.75. Conclusion: The ratio of vein dilation and age were the major predictors of fistula maturation at 3 months in our patients. The resulting online prediction model may help in clinical decision-making for patients receiving a RCAVF.